Quality of Minas fresh cheese made with milk from F1 Holstein/Zebu cows fed diets with different sources of nitrogen compounds - Ana Cássia Rodrigues de Aguiar (Arquivos do Instituto Biológico, 2017)
ABSTRACT: This study aimed to evaluate yield, fatty acid profile, physical, chemical and sensory composition of Minas fresh cheese made with milk from cows fed diets containing different sources of nitrogen compounds (soybean meal, urea, sunflower meal and detoxified castor bean meal). Eight F1 Holstein/Zebu cows with average production of 20 kg milk corrected to 3.5% fat day-1 were distributed in two 4 × 4 Latin squares, consisting of four treatments (diets), four animals and four experimental periods. Cheese was produced on the last day of each experimental period. The physical and chemical composition, yield and texture of cheese were similar between diets. The used diets influenced the concentration of fatty acid C11:0, which was higher for diets with soybean meal and sunflower meal; C18:2 C9-T11 (CLA) was higher for diets with urea, soybean meal and sunflower meal and C20:3 for diets with soybean meal and urea. For the other saturated, monounsaturated and polyunsaturated fatty acids, differences were not detected. Different sources of nitrogen compounds in the diet for cows with average production of 20 kg milk corrected to 3.5% fat day-1 have no effect on the physical or chemical composition, yield, as well as acceptance of Minas fresh cheese. However, it can influence the fatty acid profile in the cheese fat.